Kształtowanie pamięci i polityki historycznej na przykładzie przestrzeni miejskiej Budapesztu (Politeja, 2022)
Shaping of the Memory and Historical Policy in Hungary. The Case of Urban Space of BudapestNaming or changing street names (the same applies to monuments) means that certain political groups or communities can control the city. Activities in the urban space have great potential as they can lead to both community empowerment and fragmentation. Since 1989, the canon, or historical epochs to which the changing political elites at the helm of power tried to refer to by building a new urban space, also changed. The actions of Hungarian governments in the area of collective memory formation after 1989 can be described as incoherent. They leave their mark on the shape of the city, sometimes arousing consternation and sometimes the suspicion that certain decisions have a political overtone.